2020
DOI: 10.1111/ijag.15029
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of antibacterial bioactive glass nanofibers for wound healing: An in vitro study

Abstract: The present communication reports the synthesis of silver‐containing bioactive glass by sol‐gel route, followed by fabrication of the antibacterial bioactive glass nanofibers (ABGnf, dia 200‐900 nm) using electrospinning technique. The ABGnf of composition 1‐2 mol% of B2O3, 68‐69 mol% of SiO2, ~1 × 10−3 mol% of Ag2O, and 29‐30 mol% of CaO was evaluated both for wound‐healing potential and for antibacterial efficacy. An in vitro cell proliferation/migration assay was performed using SV‐transformed GM00637 (skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
5
19
0
Order By: Relevance
“…Histological analysis of the BGnf grafted wounds revealed its superiority over the control wound on the rate of wound healing process, starting from granulation tissue formation, collagen fibres arrangement, as well as the migration and proliferation of the epithelial cells to the defect site. These data were highly correlated with previous results that were reported by Saha and his group that revealed the tendency of BGnf extraction media to accelerate in vitro cell migration and proliferation rate at 24 h with a percentage that reached 82% when compared to the 47% migration rate of the control group [29]. Another study was conducted by Zhou et al [68] to compare fish col/BG nanofibers and fish col. nanofibers, as wound healing scaffolds showed a higher proliferation rate of HACAT cell line seeded on fish col/BG nanofibers.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Histological analysis of the BGnf grafted wounds revealed its superiority over the control wound on the rate of wound healing process, starting from granulation tissue formation, collagen fibres arrangement, as well as the migration and proliferation of the epithelial cells to the defect site. These data were highly correlated with previous results that were reported by Saha and his group that revealed the tendency of BGnf extraction media to accelerate in vitro cell migration and proliferation rate at 24 h with a percentage that reached 82% when compared to the 47% migration rate of the control group [29]. Another study was conducted by Zhou et al [68] to compare fish col/BG nanofibers and fish col. nanofibers, as wound healing scaffolds showed a higher proliferation rate of HACAT cell line seeded on fish col/BG nanofibers.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the degradation profile of BGnf showed a higher dissolution rate of Ca 2+ and Si ions, starting from 24 h and reached its highest level after 72 h. The study that was conducted by Saha et al [29] also showed that the BGnf ionic dissolution rate reached its highest value after 72 h; following that, it reached to a static state after 168 h that might be related to the ionic saturation of the surrounding media. Ionic dissolution contributes to the level of BG bioactivity.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“… Electrospun nanofibers of antibacterial bioactive glass/PEO for wound healing. [ 94 ] Significant cell proliferation (82%) in a period of 24 h; √Blend electrospinning; Almost two times of antibacterial activity. √Optimum rheological properties: ethanol:water (70:30), bioactive glass(BG) sol: BUTVAR® B-72 solution v/v(3:2).…”
Section: Electrospun Ultrafine Fibers For Reusable Face Masksmentioning
confidence: 99%